Bridging The Gap: Language Teacher Understanding and Responsible AI Implementation in Schools. A Case Study of English Language Educators in Kubu Raya - Tetty Novitasari Simbolon (Departement of Mathematics Education, 2024)
This qualitative case study explores the perceptions and practices of English language educators regarding the integration of artificial intelligence (AI) tools in educational settings. The study focuses on understanding how the utilization of AI impacts the professional development of language educators and how their perceptions of AI biases influence their willingness and capacity to advocate for responsible AI implementation. The study also examines the specific skill sets and knowledge domains required by language educators to effectively integrate AI tools into their pedagogical practices. Six English language educators, three high school teachers, and three lecturers in Kubu Raya, West Kalimantan, participated in the study. Data were collected through semi-structured interviews, classroom observations, and document analysis. Thematic analysis was used to analyze the data. The findings suggest that while language educators recognize the potential benefits of AI in language learning, they have concerns about biases and ethical considerations. They also feel the need for additional training and support to effectively integrate AI tools into their teaching practices. The study contributes to our understanding of how language educators perceive and engage with AI in educational settings and provides insights for the responsible integration of AI tools in language education.